2018
DOI: 10.1109/tnnls.2016.2626341
|View full text |Cite
|
Sign up to set email alerts
|

Network Unfolding Map by Vertex-Edge Dynamics Modeling

Abstract: Abstract-The emergence of collective dynamics in neural networks is a mechanism of the animal and human brain for information processing. In this paper, we develop a computational technique using distributed processing elements in a complex network, which are called particles, to solve semi-supervised learning problems. Three actions govern the particles' dynamics: generation, walking, and absorption. Labeled vertices generate new particles that compete against rival particles for edge domination. Active parti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
8
0
2
Order By: Relevance
“…In this section, we briefly introduce the particle competition model, originally proposed in 33 and improved in [34][35][36] . When investigated the behavior of this framework, it was showed that a certain level of randomness can largely enhance the learning process, similar to the phenomenon of stochastic resonance, in which the performance of a nonlinear deterministic system can be largely improved by a certain level of noise 4 .…”
Section: Community Detection By Particle Competitionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we briefly introduce the particle competition model, originally proposed in 33 and improved in [34][35][36] . When investigated the behavior of this framework, it was showed that a certain level of randomness can largely enhance the learning process, similar to the phenomenon of stochastic resonance, in which the performance of a nonlinear deterministic system can be largely improved by a certain level of noise 4 .…”
Section: Community Detection By Particle Competitionmentioning
confidence: 99%
“…Therefore, depending on the system complexity, the use of only deterministic rules might be insufficient to learn the process behind the system 4 . A recent development of this framework showed that it can identify nonlinear features in boundaries between classes with overlapping structural data 36 . Although other community detection algorithms could be selected in this work, the particle competition method was adopted due to its performance in overlapping data and low computational complexity order, which is lower than other network-based semi-supervised algorithms 34,36 .…”
Section: Community Detection By Particle Competitionmentioning
confidence: 99%
See 1 more Smart Citation
“…A presença e o estudo de estrutura de comunidades são comumente encontrados em diversas redes reais, tais como redes sociais, redes de interação de proteínas na biologia e na bioinformática (JONSSON et al, 2006;ZHANG, 2009), estruturas de fluxo óleo-água (GAO et al, 2015), redes de mobilidade humana (THIEMANN et al, 2010), estrutura espacial de movimento urbano em grandes cidades (ZHONG et al, 2014), redes de elites corporativas nos campos da política e da economia (HEEMSKERK; TAKES, 2016), e muito mais. Comunidades, também conhecidas como estruturas modulares, são comumente definidas como sendo grupos de vértices densamente conectados (CLAUSET; MOORE, 2004;GIRVAN, 2004;COSTA et al, 2007;BLONDEL et al, 2008;FORTUNATO, 2010;LANCICHINETTI et al, 2010;ZHAO, 2012c;MACAU;RUBIDO, 2016;ZHAO, 2016).…”
Section: Detecção De Comunidades Via Remoção Iterativa De Arestasunclassified
“…Encontrar a partição ótima é considerado um problema NP-difícil na maioria dos casos (FORTUNATO, 2010), consequentemente abrindo espaço para ampla pesquisa em meios de se encontrar soluções sub-ótimas em tempo admissível. Diferentes abordagens para detecção de comunidades já foram desenvolvidas, incluindo propriedades espectrais em matrizes de grafos (DONETTI;MUñOZ, 2004;CAPOCCI et al, 2005;YANG;LIU, 2008;MITROVIć;TADIć, 2009), sincronização de osciladores acoplados (ARENAS; DíAZ-GUILERA; PéREZ-VICENTE, 2006), modelo de Potts (REICHARDT; BORNHOLDT, 2004), caminhada e competição de partículas em redes (QUILES et al, 2008;BREVE;QUILES, 2009;ZHAO, 2012c;ZHAO, 2016;VERRI;URIO;ZHAO, 2016), e dinâmica de partículas com forças de atração e repulsão (QUILES; MACAU; RUBIDO, 2016).…”
Section: Detecção De Comunidades Via Remoção Iterativa De Arestasunclassified